ANALISIS KEPUASAN PENGUNJUNG MENGGUNAKAN SECOND ORDER CONFIRMATORY FACTOR ANALYSIS PADA STRUCTURAL EQUATION MODELING (Studi Kasus: Pengunjung Pemandian Air Panas (PAP) Guci) - Niken Anggraini Dewi; Rita Rahmawati; Moch. Abdul Mukid (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
Pemandian Air Panas (PAP) Guci is one of the famous natural destinations in Tegal regency. The visitors are fluctuated. Therefore, the writer carried out an analysis of visitor satisfaction using Stuctural Equation Modeling (SEM). Confirmatory factor analysis using in the reseach is second order. The construct used are the service quality (tangibles, reliability, responsiveness, insurance, and empathy), product quality (facilities, accessibility, source human and hygiene), price (affordability, suitability, and price comparisons), visitor satisfaction (overall satisfaction, satisfaction as expected, and the employee), and the interest reset. Choosing variables based on justification theory. Significant parameters, namely the quality service to the quality products by 50,8%, the quality product to the prices by 89%, the price to the visitor satisfaction of 91,4%, visitor satisfaction to the interest reset of 55%. Parameters were not significant, envelop service quality to price, quality service to visitor satisfaction, and quality product to visitor satisfaction. Keywords: Second Order Factor Analysis, SEM, Product Quality, Service Quality, Price, Visitor Satisfaction, Interest Reset.